Editorial - Dmitry A. Medvedev (Chimica Techno Acta)
In this year, the Chimica Techno Acta journal (CTA) celebrates its 10th anniversary. A tenth of a century is a long time, during which about 350 papers have been published. In the beginning, the journal has been edited in two formats (electronic and print) and in two languages (Russian and English), but then considerable efforts have been made to ensure the rapid consideration of manuscripts while maintaining high peer-review standards at the same time. CTA has become an exclusively English-language and online journal. As a result, authors currently receive a first decision on their manuscripts within 17 days of submission, while the total time from submission to publication of a final version does not exceed 50 days. Along with providing good conditions for our authors, the journal seeks all possible ways to improve the quality of its content by considering well-designed manuscripts for their publication. Therefore, the rejection rate is increased from 10–20% in 2014–2015 to almost 50% in 2022.